Determinants market price of indigenous veld goats in Limpopo Province, South Africa - Mugwabana, Thinawanga Joseph (My University, 2025)
Market price is a key factor that determines revenue generation and the potential profitability of the enterprise. The aim of this study was to analyse determinants of market price in indigenous veld goats in Limpopo Province, South Africa. The study had three objectives: (1) to determine the socio-economic characteristics of indigenous veld goat farmers in Limpopo Province, (2) to analyse the determinants of market price of indigenous veld goats in Limpopo Province, and (3) to describe conditions that will lead to high market price for indigenous veld goats in Limpopo Province. The study was conducted in the five districts of Limpopo Province, namely: Vhembe, Mopani, Capricorn, Sekhukhune and Waterberg. The study used a quantitative approach that followed a cross-sectional design where the data was collected once from IVG farmers. The study targeted all the 86 active members of the Limpopo IVG farmers’ club, however, only 35 voluntarily participated in the study, representing a response rate of 41%. The data was analysed using SPSS (version 28) and the results presented using descriptive (frequencies) and inferential (t-test and regression) statistical techniques. The descriptive study results found that male farmers dominate (85.7%) in the goat farming sector in Limpopo Province. The majority (28.6%) are retirees that farm with goats on a part-time basis (54.3%). While most of the IVG farmers (65.7%) have tertiary education, only a quarter of them (25.7%) had formal training on goat production. Land ownership by IVG farmers is predominantly communal (62.9%) with private ownership being less common (37.1%). The main source of capital for acquiring goats is through savings (85.7%) and the most number of goats owned (34.2%) averages between 21-49 goats per herd. The inferential study results identified five key independent variables that significantly influence the market price of indigenous veld goats, namely: body condition score, female physiological state, herd size, distance to the market and iv | P a g e type of farming system. These independent variables significantly positively influence the market price with the exception of the female physiological state. However, for optimal market price in IVG it is important to consider all other factors despite their significant status, for as long as they have an influence in the market price of goats. This research contributes to the body of knowledge on determinants of market price in indigenous veld goats in Limpopo Province and to some extend throughout South Africa.
Thesis (MBA.) -- University of Limpopo, 2025
Keywords: Smallholder farmers; Goat production; Determinants; Market price; Indigenous veld goats; Goat farming; Farm ownership; Farm ownership -- South Africa; Farms, Small; Farmers - South Africa -- Limpopo; Markets